The Legality of the Evidence as a Condition of its Admissibility in Lithuanian Civil Procedure - Nekrošius, Vytautas (Teisė, 2021)
In the article the author, using comparative as well as other methods of scientific research, analyses the issues related to the admissibility of illegally obtained evidence in civil proceedings. The author intends to answer the question of whether the doctrine of the “fruits of the poisonous tree” is applied in Lithuania and, if so, to what extent.